Dialogue Language Style of the Qur'an "A Stylistic Analysis of Dialogues on the Truth of the Qur'an" - Abd Rahim (Solo International Collaboration and Publication of Social Sciences and Humanities, 2023)
Dialogue or Uslub al-Hiwar is the most prominent language style used by the Qur'an in presenting arguments and proofs of the truth of Islamic teachings. Both evidence of the oneness of God, the truth of the messenger and evidence of the truth of the Qur'an. This research is an Arabic stylistic analysis of the variety of language styles in the sentences in the Qur'an, especially the theme of the truth of the Qur'an. The method used in this research is a descriptive qualitative method to reveal how the two parties to the dialogue use various styles of language in conveying their arguments. In this study, it was found that there were various styles of language used by the two dialogues in conveying their attitudes. Starting from the variety of language styles of equality, opposition, majaz mursal and others.